Implementasi Algoritma Prim Dalam Penentuan Ikatan Senyawa Kimia - Olivia Benazir Ester Tiwow; Adhi Kusnadi (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
This research concerns the implementation of Prim algorithm in the determination of bond of a chemical compound. By doing a minimum spanning tree search of a weight graph that has been created. Input from the user in the form of chemical compounds will be processed so that the compound can be divided into elements that will act as nodes on the prime algorithm. Weight of the tangent node is obtained from the comparison of the minimum number of atoms that can react between the two elements that will be bonded to each other. Applications developed on the basis of the web by considering the functionality of the design can be accessed by many people. System design is poured into HTML and Javascript programming language. All design functionality is poured into the Javascript programming language. This study is still limited to programs that can only process the input of compounds that are in class A in the periodic table. And preformed compounds such as SO42-, HO3-. This application has an accuracy rate of 77.41% and 66.67% of testers said that this application is useful for Indonesian education. Index Terms—Chemical Compound, prim algoritm, minimum spanning tree, website, Javascript.